HtrA2/Omi: potential therapeutic targets for neurodegenerative diseases - Xu, Liting; Zeng, Min (Frontiers in Pharmacology, 2026)
High temperature requirement protein A2 (HtrA2/Omi), a key regulator of mitochondrial quality control, plays a pivotal role in determining cell fate through its subcellular localization, whether mitochondrial or cytosolic. Growing evidence links the absence or dysfunction of HtrA2 to the pathogenesis of neurodegenerative diseases. This review examines the structure and function of HtrA2, highlights its transcriptional regulators, explores its involvement in neurodegeneration, and outlines the currently identified agonists and inhibitors, offering new insights for developing HtrA2/Omi as a potential therapeutic target for neurodegenerative disorders.